Surface characteristics, adhesive penetration analysis and bending strength properties of 2-ply laminated bamboo strips of Buloh Semantan (Gigantochloa scortechinii) / Nurizzaati Saharudin - Saharudin, Nurizzaati (2010)
Bamboo is a multipurpose plant that has a centuries-long documented history of application. Its unique properties had qualified it to enthrone as a valuable natural resource with many purposes and hundred of uses. Bamboo composite lumber (BCL) for example, is the most potential non-timber forest product to join wood for various uses. BCL is a reconstituted wood which is made by laminating series of bamboo in a lumber like material with adhesive. In bamboo laminated field, understanding of the adhesive bonding and adhesion characteristics will lead to better utilization of bamboo as a material for composite product. The purposes of this study were to analyze the adhesive penetration of bamboo and its correlation towards the bending strength of laminated bamboo as well as to determine the surface characteristics of the material i.e. the wettability and buffer capacity. Matured Buloh Semantan aged three years old was used for this study. All specimens were tested at 9 to 10% of MC and were performed separately according to its portions, parts and levels of pressure. The average mean pH value of Buloh Semantan is 6.23. The buffer capacity was 0.30 me and it is more acid than of alkali. The phenol-formaldehyde resin was used in this study because Buloh Semantan is more suitable with an alkaline resin, than acid curing resin, urea-formaldehyde. The contact angle of Buloh Semantan using distilled water was not significantly different from portions and parts (p> 0.05). The average contact angle was 51.84°. Generally, the adhesive penetration was highly significantly different between parts and levels of pressure but slightly significant at different portions. Adhesive penetration was greater with samples from I-I part and bottom portion. For comparison between levels of pressure, it showed that the adhesive penetration is proportionate to the increasing amount of force applied. It continuously increased until it reaches its ultimate load.